Effect Of Pelvic Floor Muscle Training On Uterus Involution In Spontane Postpartum Mother - Intan Yusita; Jusuf Effendi; Achadiyani (Health Media, 2020)
Childbirth is a natural occurrence experienced by every pregnant woman. Postpartum mothers have problems with uterine involution. One activity that is recommended for mothers after childbirth is the puerperal exercises Pelvic Floor Muscle Treatment (PFMT) or exercises specifically performed for pelvic floor muscles. The research method uses quasy experiment with one group post test design with control. The total sample is 36 people. Sampling technique is done by consecutive sampling with random permutation block. The instrument of data collection that is observational sheet is doing direct observation to the object of research to look closely at the activities carried out. Observation sheet which includes Pelvic floor muscle training. Pelvic Floor Muscle Training exercises affect the acceleration of decreased uterine fundus height (TFU) in Postpartum mothers compared to not doing gymnastics. Health workers should try to provide counseling and counseling about the importance of Pelvic floor muscle training.